2020
DOI: 10.14791/btrt.2020.8.e18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of High-Grade Glioma with Primary Leptomeningeal Seeding at Initial Diagnosis in a Single Center Study

Abstract: Background High-grade glioma (HGG) with primary leptomeningeal seeding (PLS) at initial diagnosis is rare. The purpose of this study was to identify its clinical features and to describe the clinical treatment outcomes. Methods We retrospectively reviewed the medical records of patients with HGG (World Health Organization grade III or IV) at our institution between 2004 and 2019, and patients with PLS at the initial diagnosis were enrolled in the study. Clinical feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Mandel et al documented similar ndings, reporting that a combination of chemotherapy and radiotherapy led to prolonged overall survival of 7.7 months, which was increased compared to monotherapy or supportive care [7,24]. Kwon et al found that given the aggressive nature of LMD, patients who are diagnosed with LMD at the time of GBM diagnosis should undergo radiotherapy and chemotherapy earlier and more aggressively than in patients without LMD [25]. The low prevalence of LMD has proven to be an obstacle in examining the e cacy of various treatments.…”
Section: Adjuvant Treatment Of Lmd In Gbmmentioning
confidence: 89%
See 1 more Smart Citation
“…Mandel et al documented similar ndings, reporting that a combination of chemotherapy and radiotherapy led to prolonged overall survival of 7.7 months, which was increased compared to monotherapy or supportive care [7,24]. Kwon et al found that given the aggressive nature of LMD, patients who are diagnosed with LMD at the time of GBM diagnosis should undergo radiotherapy and chemotherapy earlier and more aggressively than in patients without LMD [25]. The low prevalence of LMD has proven to be an obstacle in examining the e cacy of various treatments.…”
Section: Adjuvant Treatment Of Lmd In Gbmmentioning
confidence: 89%
“…Onuma et al noted that, while VP shunt surgery did not improve KPS in 10 GBM patients with hydrocephalus, 6 of 10 patients did experience subjective improvement in symptoms [38]. Kwon et al also noted that patients experienced less pain following CSF diversion [25]. Given that treatment at this stage of GBM is supportive and not curative, symptomatic improvement is signi cant for patients and should be considered by neuro-oncologists in concert with neurosurgeons.…”
Section: Surgical Treatment Of Lmd In Gbm Hydrocephalus Vp Shuntmentioning
confidence: 99%